2008
DOI: 10.1017/s000273160004227x
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of Hafting Adhesive on a Slotted Antler Point from a Southwest Yukon Ice Patch

Abstract: This article describes the identification of a hafting adhesive on an antler point, slotted for microblade insertion. The adhesive, found in the slots of the point, would have held the microblades in place. Radiocarbon dated to 7310 ± 40 B.P. (uncalibrated), the point is one of the oldest and best-preserved artifacts recovered from the melting alpine ice patches in southwestern Yukon, Canada. Because the artifact was frozen, the organic components have not degraded and a detailed chemical analysis was possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 19 publications
(20 reference statements)
0
29
0
1
Order By: Relevance
“…Their presence is characteristic of a Pinus origin (Helwig et al . ). Whether the diterpenoid substances correspond to a tar, an oxidized resin or a resin is quite difficult to determine.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Their presence is characteristic of a Pinus origin (Helwig et al . ). Whether the diterpenoid substances correspond to a tar, an oxidized resin or a resin is quite difficult to determine.…”
Section: Resultsmentioning
confidence: 97%
“…; Osete‐Cortina and Doménech‐Carbó ; Helwig et al . ; Steigenberger and Herm ). In addition, α‐ and β‐seco‐dehydroabietic acids, pimaric acid—sometimes present in noticeable amounts—and isopimaric acid were identified in five samples.…”
Section: Resultsmentioning
confidence: 98%
“…Indeed, higher molecular weight compounds ( e.g. , >C 20 such as abietic acids) have often been targeted in past archaeological adhesive studies . In this study, phenanthrene, naphthalene and their respective derivatives were identified in high abundance, which have been proposed as potential volatile degradation products of abietic acids .…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies of archaeological residues have typically relied on extraction and derivitization [5,9,10]. However, the development of a non-destructive direct HS-SPME extraction from the residue is a substantial benefit, as further analyses can then be conducted on the item in its original state after it has been screened by VOC analysis.…”
Section: Sample Extraction Techniquesmentioning
confidence: 99%
“…Finally, an ideal method of analysis should be non-destructive in order to preserve the sample if other testing is required. Despite being a particularly challenging area of research, GC-MS has been employed successfully in numerous archaeological investigations including, but not limited to, the analysis of smoking pipe residue from ancient burials [6], ceramics [7], plasters [7], resins [2,5,[8][9][10], and resin additives, such as beeswax [9,11].…”
Section: Introductionmentioning
confidence: 99%